Suitability of IBS formwork system in Malaysian construction industry - Mohd Nawi, Mohd Nasrun; Mydin, M.A. Othuman; Mohamed Elias, Ezanee; Mohd Shaharanee, Izwan Nizal; Yusoff, Mohd. Nazaruddin (INSInet Publications, 2015)
Sector-based building industry or IBS (Industrialised Building System) is still considered relatively new in Malaysia.Although this system has long been used in developed countries such as in Europe. Based on previous studies, the main element that attracted many developers to use the system is a factor in terms of construction time, quality and cost.Generally, this system is divided into five main categories: prefabricated concrete frame systems, panel and box, steel frame system, the system box, steel form work system-block and wood framing systems. This paper discusses the types of systems steel box (steel formwork system) which also covers the installation procedures and work plans based on the concept of IBS.This study was conducted on mega construction projects in and around Kuala Lumpur and Selangor.The result deduced through analysis of usage statistics according to classification system box in construction projects.